The Effect of Price and Visual Design on Purchasing Decisions and Its Implications on Consumer Satisfaction of Virtual Items in the Online Game Mobile Legends: Bang Bang Among Gen Z in Pontianak City - Ade Muammar Ichlasul Amal; Fita Kurniasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In today's world, technology is rapidly advancing, especially among young people. Gaming has developed significantly in Indonesia, particularly in Mobile Legends. Therefore, this study was conducted to determine and analyze the influence of price and visual design on purchasing decisions virtual items. The implications of the Mobile Legends game on consumer satisfaction among Gen Z players of Mobile Legends in Pontianak City. The method used is quantitative, using Structural Equation Modeling (SEM) as a data analysis method, using the Smart-PLS 4 application. Data collection was carried out through distributing questionnaires on Google Form which were shared through closest friends, social media and mobile legends players who played in coffee shops, using a Likert scale, distributing a sample of 100 respondents. This study concluded that price had a significant effect on purchasing decisions with a significant value of 0.024 <0.05. Visual design had a significant effect on consumer satisfaction with a significant value of 0.032 <0.05. Purchasing decisions had a significant effect on consumer satisfaction with a significant value of 0.033 <0.05.